The Relationship Between Family Support and Compliance with Iron Chelation Medication in Thalassemia Adolescents - Ashvia, Rahil; Casman, Casman; Rosmaitaliza , Rosmaitaliza; Sudrajat , Andi; Arjuna, Arjuna; Kastino, Rina (STIKES Hesti Wira Sriwijaya, 2026)
Introduction: Treatment adherence is a significant challenge for thalassemia patients. Iron chelation medication must be taken for life, and therefore, family support is essential to achieve adherence. To determine the relationship between family support and iron chelation medication adherence in thalassemia patients. Method: This study used a quantitative cross-sectional approach. Data were collected using a questionnaire from a sample of 120 respondents. Results: The statistical test yielded a p-value of 0.027 <0.05, concluding that there is a significant relationship between family support and iron chelation medication adherence in adolescents with thalassemia. Most family support was categorized as good, and on average, adolescent thalassemia patients were considered compliant Conclusion: Family support is related to medication adherence. Therefore, families are expected to continuously monitor and provide attention to their sick family members and consistently remind them to take their medication.